Effect of ramadan fasting on body weight and percent of body fat among student from program nutrition study of UPN “Veteran” Jakarta, Indonesia - Ayu Nurjanah Wida; Wahyuningsih Utami; Quratul Marjan Avliyah; Fransiske Simanungkalit Sintha (BIO Web of Conferences)
Background: Overweight is a state of unbalanced body health caused by excess fat accumulation and can interfere with health. The prevalence of overweight year 2013 in Indonesia at the age of more than 18 years, namely 13.3%, increased in 2018 to 13.6%. This study aims to see the effect of Ramadan fasting on body weight and percent body fat in college students. The research design used was a quasy experimental design with one group pretest and posttest. The number of subjects was 137 UPN "Veteran" Jakarta nutrition students with ages over 18 years. Data collection was carried out 3 times, namely before fasting, the second week of fasting and after one month of fasting ended. The instruments used are BIA (Bioelectrical Impedance Analysis), a 24-hour food record and PAL (Physical Activity Level). Data analysis used the Wilcoxon test and paired t test. The results obtained include: (1) there was difference between body weight before fasting and body weight during fasting in p value = 0.000 (p <0.05). Likewise, there was a difference between body weight before fasting and body weight one month after the end of the Ramadan fast in p value = 0.048 (p <0.05). (2) there was difference between percent of body fat before fasting and percent of body fat during fasting in p value = 0.000 (p <0.05). Likewise, there was difference between percent of body fat before fasting and percent of body fat one month after the end of the Ramadan fast in p value = 0.048 (p <0.05). In conclusion, Ramadan fasting can affect body weight and percent of body fat.